2018
DOI: 10.1096/fj.201801463r
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of femurs from mice embarked on board BION‐M1 biosatellite reveals a decrease in immune cell development, including B cells, after 1 wk of recovery on Earth

Abstract: Bone loss and immune dysregulation are among the main adverse outcomes of spaceflight challenging astronauts' health and safety. However, consequences on B‐cell development and responses are still under‐investigated. To fill this gap, we used advanced proteomics analysis of femur bone and marrow to compare mice flown for 1 mo on board the BION‐M1 biosatellite, followed or not by 1 wk of recovery on Earth, to control mice kept on Earth. Our data revealed an adverse effect on B lymphopoiesis 1 wk after landing. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 38 publications
(44 reference statements)
0
27
0
1
Order By: Relevance
“…Even if our sample size is small, it is tempting to put this observation in parallel with the study that showed that 46% of the astronauts who stayed 6 months on board the ISS encountered immunological changes 2 . Additionally, differences in V(D)J recombination effector signatures observed in COS4 and COS5 suggest a modification of B lymphopoiesis in these two subjects, as observed in mice that spent 30 days onboard the BION‐M1 satellite 23 . Interestingly, these two subjects, as well as the BION‐M1 mice, 53 developed a stress response, and it was shown that exposure to glucocorticoids has a rapid effect on B lymphopoiesis because the administration of corticosterone induces a loss of 30%‐70% in 24 hours among murine early pro‐B, pre‐B, and immature B cells 54 .…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Even if our sample size is small, it is tempting to put this observation in parallel with the study that showed that 46% of the astronauts who stayed 6 months on board the ISS encountered immunological changes 2 . Additionally, differences in V(D)J recombination effector signatures observed in COS4 and COS5 suggest a modification of B lymphopoiesis in these two subjects, as observed in mice that spent 30 days onboard the BION‐M1 satellite 23 . Interestingly, these two subjects, as well as the BION‐M1 mice, 53 developed a stress response, and it was shown that exposure to glucocorticoids has a rapid effect on B lymphopoiesis because the administration of corticosterone induces a loss of 30%‐70% in 24 hours among murine early pro‐B, pre‐B, and immature B cells 54 .…”
Section: Discussionmentioning
confidence: 56%
“…2 Additionally, differences in V(D)J recombination effector signatures observed in COS4 and COS5 suggest a modification of B lymphopoiesis in these two subjects, as observed in mice that spent 30 days onboard the BION-M1 satellite. 23 Interestingly, these two subjects, as well as the BION-M1 mice, 53 developed a stress response, and it was shown that exposure to glucocorticoids has a rapid effect on B lymphopoiesis because the administration of corticosterone induces a loss of 30%-70% in 24 hours among murine early pro-B, pre-B, and immature B cells. 54 Thus, an individual's stress perception and response is a likely contributor to IgM repertoire changes, as previously shown for viral reactivation.…”
Section: F I G U R Ementioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a higher level of physical activity is beneficial to preventing bone loss for perimenopausal women 25 . Spaceflight leads astronauts to significant bone loss, which demonstrates that weightlessness results in decrease in bone mass 26 . Given that orthodontic force induces alveolar bone remodelling leading to tooth movement, OTM is an ideal animal model exploring how osseous tissue responds to controlled force.…”
Section: Discussionmentioning
confidence: 99%
“…The humoral response mediated by B lymphocytes is not well studied. These cells appear to be minimally involved during spaceflight, since their frequency does not change during flight but seems to be reduced on return to Earth (Tascher et al, 2019). No changes in the immunoglobulin repertoire were observed in mice (Ward et al, 2018) and space travelers studies (Stowe et al, 1999;Rykova et al, 2008).…”
Section: Gut Microbiome and Immune System Declinementioning
confidence: 90%